What do we need to know about anatomy in gynaecology: A Delphi consensus study. (February 2020) - Koppes, Dorothea M.; Triepels, Charlotte P.R.; Schepens-Franke, Annelieke N.; Kruitwagen, Rutgerus F.P.M.; Van Gorp, Toon; Scheele, Fedde; Notten, Kim J.B.
Abstract: Objective: Determination of the anatomical structures that should be taught to ensure safe and competent practice among general gynaecologists. Study Design: A two-round Delphi survey, face-to-face meeting in focus groups and an individual interview. Participants were medical doctors and trainees from gynaecology, surgery, urology and radiology from academic, non-academic teaching and non-academic, non-teaching hospitals in the Netherlands. Relevant structures were collected from gynaecology surgery atlas based on most common gynaecological surgeries and diseases. These structures were supplemented and critically viewed in focus groups followed by a Delphi survey. In the Delphi survey gynaecologist and trainee's gynaecology from all over the Netherlands scored the items on a Likert scale between 1 (not relevant) and 5 (highly relevant). Consensus was defined when ≥ 70 % of the panellist scored the item as relevant or very relevant and the average rating was ≥ 4. Main outcome was clinically relevant anatomical structures. Results: Consensus on 86 clinically relevant anatomical structures divided by nine categories. Conclusions: This study identified a core list of anatomical structures that are relevant to the safe and competent practice of general gynaecologists and that can be used to guide gynaecology postgraduate education. This is the first step in a much wider and complex process of becoming a competent gynaecologist.